Comparison of Three Non-Invasive Transcranial Electrical Stimulation Methods for Increasing Cortical Excitability - Inukai, Yasuto; Saito, Kei; Sasaki, Ryoki; Tsuiki, Shota; Miyaguchi, Shota; Kojima, Sho; Masaki, Mitsuhiro; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Human Neuroscience, 2016)
Transcranial direct current stimulation (tDCS) is a representative non-invasive brain stimulation method (NIBS). tDCS increases cortical excitability not only in healthy individuals but also in stroke patients where it contributes to motor function improvement. Recently, two additional types of transcranial electrical stimulation (tES) methods have been introduced that may also prove beneficial for stimulating cortical excitability; these are transcranial random noise stimulation (tRNS) and transcranial alternating current stimulation (tACS). However, comparison of tDCS with tRNS and tACS, in terms of efficacy in cortical excitability alteration, has not been reported thus far. We compared the efficacy of the three different tES methods for increasing cortical excitability using the same subject population and same current intensity. Fifteen healthy subjects participated in this study. Similar stimulation patterns (1.0 mA and 10 min) were used for the three conditions of stimulation (tDCS, tRNS, and tACS). Cortical excitability was explored via single-pulse TMS elicited motor evoked potentials (MEPs). Compared with pre-measurements, MEPs significantly increased with tDCS, tACS, and tRNS (p < 0.05). Compared with sham measurements, significant increases in MEPs were also observed with tRNS and tACS (p < 0.05), but not with tDCS. In addition, a significant correlation of the mean stimulation effect was observed between tRNS and tACS (p = 0.019, r = 0.598). tRNS induced a significant increase in MEP compared with the Pre or Sham at all time points. tRNS resulted in the largest significant increase in MEPs. These findings suggest that tRNS is the most effective tES method and should be considered as part of a treatment plan for improving motor function in stroke patients.